The Effect of Temperature on Manufacturing Process of Tannin Acid-Based Adhesive Materials on Mechanical and Physical Properties - Perdana, Mastariyanto; Abral, Hairul; Son, Lovely; Masruchin, Nanang; Azmi, Muhammad; Kadriadi, Kadriadi (Green Engineering Society, 2026)
This study focuses on the development and characterization of adhesives based on Polyvinyl Alcohol (PVA), Tannic Acid (TA), and Cellulose Nanofibre (CNF). The main objective is to optimize the temperature used in the production process. Phenol-formaldehyde and other synthetic adhesives frequently encounter environmental obstacles, necessitating the search for more ecologically sound alternatives. TA, a naturally occurring polyphenolic molecule, has significant potential as an eco-friendly glue ingredient. This study assesses the impact of temperature fluctuations (30, 45, 60, 75, and 90°C) during the glue manufacturing process on its mechanical characteristics, specifically emphasizing shear stress. Experiments were conducted at a rotational speed of 1500 revolutions per minute (RPM) for 30 minutes. The results indicated that the adhesive performed best at 90°C, achieving a maximum shear stress value of 3.41 MPa. The results demonstrated a significant enhancement in the shear strength of the bioadhesive, exhibiting an approximately sixfold increase as the processing temperature was elevated from 30°C to 90°C. Microstructural analysis reveals that the voids formed during the mixing process decrease at this specific temperature. The results indicate that elevated temperatures lead to a significant reduction in void formation. The FTIR measurement revealed the absorption of hydroxyl groups around 3305 cm⁻¹, suggesting the presence of robust crosslinking. Furthermore, elevated temperatures lead to a significant reduction of free OH- groups within the bioadhesive. The PVA/TA/CNF adhesive possesses extensive potential for application in industries that necessitate adhesives with exceptional strength. The study is anticipated to offer comprehensive understanding of how to improve the manufacturing process of TA-based adhesives, and its impact on the creation of adhesive materials that are more sustainable and environmentally friendly.